2021
DOI: 10.3390/radiation1020009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Biological Dosimetry for Monitoring Medical Workers Occupationally Exposed to Ionizing Radiation

Abstract: Medical workers are the largest group exposed to man-made sources of ionizing radiation. The annual doses received by medical workers have decreased over the last several decades, however for some applications, like fluoroscopically guided procedures, the occupational doses still remain relatively high. Studies show that for some procedures the operator and staff still use insufficient protective and dosimetric equipment, which might cause an underestimation of medical exposures. Physical dosimetry methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Dicentric chromosomes without accompanying fragments and pericentric inversions were also detected, both representing long-lived chromosome aberrations from past exposure ( 21 , 22 ). Numerous studies support our findings of increased rate of chromosome aberrations and high interindividual variability ( 23 , 24 , 25 ), which is attributed to differences in genetic susceptibility towards ionising radiation ( 26 , 27 , 28 , 29 , 30 , 31 , 32 ), activation of DNA repair ( 33 , 34 ), and anti-inflammatory processes ( 35 ). Lymphocyte chromosome aberrations in our occupationally exposed participants whose annual doses did not exceed risk limits can also be attributed to cumulative effects of chronic exposure to low-dose ionising radiation ( 36 ).…”
Section: Resultssupporting
confidence: 87%
“…Dicentric chromosomes without accompanying fragments and pericentric inversions were also detected, both representing long-lived chromosome aberrations from past exposure ( 21 , 22 ). Numerous studies support our findings of increased rate of chromosome aberrations and high interindividual variability ( 23 , 24 , 25 ), which is attributed to differences in genetic susceptibility towards ionising radiation ( 26 , 27 , 28 , 29 , 30 , 31 , 32 ), activation of DNA repair ( 33 , 34 ), and anti-inflammatory processes ( 35 ). Lymphocyte chromosome aberrations in our occupationally exposed participants whose annual doses did not exceed risk limits can also be attributed to cumulative effects of chronic exposure to low-dose ionising radiation ( 36 ).…”
Section: Resultssupporting
confidence: 87%
“…Improvement of practices and devices over time can influence exposure time. That is the reason why the mean annual effective doses has decreased during the period from 2007 to 2011 between Burkina Faso [8] and Nigeria [23]. However, we observe that in the year 2007, at the level of the diagnostic radiology sector, several countries presented the highest annual dose mean values [12,15,23].…”
Section: Discussionmentioning
confidence: 80%
“…The largest size of the source populations was 5152, provided in the field of diagnostic radiology by Ghana between 2000 and 2009. It was followed by Tanzania with 757 diagnostic radiology workers of 1000, while Tapsoba et al [8] reported only 81 medical workers of 157, in Ouagadougou at Burkina Faso. The different studies reported data on workers exposed to ionising radiation in all fields using ionising radiation, but more particularly in different specialities from medical sectors (table 2).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…This test is used in health surveillance to characterize the general health of the worker and, also can detect a variety of disorders such as infections, anemia, diseases of the immune system, and blood p. 4 PAG cancers. As a consequence of their radiosensitivity and high cell renewal rate (from hours to days), leukocytes and platelets are blood components that could characterize possible damage due to exposure to ionizing radiation [1,6,7]. However, the CBC test is not the most suitable biomarker, as it requires doses over the limits established as safe to exposed workers by international organizations to damage the components of peripheral blood [8][9][10].…”
Section: Introductionmentioning
confidence: 99%